Peran Influencer Dan Minat Investasi Pada Generasi Sandwich Di DKI Jakarta - Ester Anabel, Leora (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
A This study aims to investigate the role of social media influencers in the stock investment decision-making process of the Sandwich Generation and its impact on their investment interest. The Sandwich Generation consists of individuals who are responsible for both aging parents and young children, resulting in complex financial responsibilities. The primary focus of the research is on how social media influencers, with a large following, provide insights, recommendations, and investment information through social media platforms. This study adopts both qualitative and quantitative approaches, collecting data from members of the Sandwich Generation involved in stock investments. The data encompasses the influence of social media influencers on investment decision-making, their investment interest, and factors influencing investment decisions. The hope is that the results of this research can provide in-depth insights into how the role of social media influencers affects the stock investment decisions of the Sandwich Generation and shapes their investment interests. Furthermore, this research is expected to offer valuable understanding for influencers, stakeholders in the investment world, and contribute to the development of better financial literacy strategies for the Sandwich Generation.